Potensi Rumput Laut Dalam Menghambat Pertumbuhan Jamur Aspergillus flavus - KETUT SRIE MARHAENI JULYASIH; ARIKA PURNAWATI (Fakultas Pertanian Universitas Udayana, 2019)
Potential of Seaweed in the Inhibition of Fungi Growth Aspergillus flavus. This use of synthetic chemicals as a controller of fungal growth in foodstuffs can have adverse effects on health, so it needs natural control ingredients that do not have an impact on human health. Various types of fungi such as Aspergillus flavus attack a lot of food items after harvest, these fungi can produce aflatoxin which is very toxic to consumers. Aflatoxin cannot be neutralized through cooking so efforts to avoid fungal contamination need to be done. One of the natural fungi controllers is by utilizing natural resources, including seaweed. Development of seaweed as an antifungal is an alternative that needs to be realized. For this reason, it is necessary to examine the potential inhibitory of seaweed A. flavus development. This study examined six types of seaweed like Gracilaria verrucosa, Euchema spinosum, Ulva lactuca, Ulva reticulata, Euchema edule, and Padina sp. The results showed that Padina sp. seaweed has a very strong potential inhibitory compared to other types of seaweed.